Respostas
respondido por:
1
log3(-x²-2x)= 0
3 elevado a zero é 1
(-x²-2x)=1
-x²-2x-1=0
delta=4-4x1
delta=0
X=-(-2)/-2
X'=-1
X''=1
3 elevado a zero é 1
(-x²-2x)=1
-x²-2x-1=0
delta=4-4x1
delta=0
X=-(-2)/-2
X'=-1
X''=1
respondido por:
2
log (-x²-2x)=0
3
- x² - 2x = 3^0
- x² - 2x - 1 = 0(-1)
x² + 2x + 1 = 0
delta= 2^2 - 4.1.1= 4 -4= 0
x = - 2 +/- V0 ==> - 2 +/- 0
2.1 2
x1 =x2 = -2
2
x1 = x2 = - 1
luizftbl:
delta=b²-4.a.c
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás